Synthesis and Electrical Properties of TiO2 Nanoparticles Embedded in Polyamide-6 Nanofibers Via Electrospinning - Nirmala, R.; Jeong, JinWon; Navamathavan, R.; Kim, Hak Yong (Nano-Micro Letters, 2011)
We report on the synthesis and characterizations of TiO2 nanoparticles embedded in polyamide-6 composite nanofibers by using electrospinning technique. The influence of substrate on the electrical characteristics of polyamide-6/TiO2 composite nanofibers was investigated. The resultant nanofibers exhibit good incorporation of TiO2 nanoparticles. The doping of TiO2 nanoparticles into the polyamide-6 nanofibers were confirmed by high resolution transmission electron microscopy and energy dispersive X-ray spectroscopy. Photoluminescence (PL) and cathodoluminescence (CL) spectroscopy were also used to characterize the samples. The PL and CL spectra reveal that the as-spun polyamide-6/TiO2 composite nanofibers consisted of overlapping of two broad emission bands due to the contribution of polyamide-6 (centered at about 475 nm), which might originate from organic functional groups of polyamide-6 and TiO2 nanoparticles (centered around 550 nm). The electrical conductivity of the polyamide-6/TiO2 composite nanofibers on different substrates was carried out. It was found that the electrical conductivity of the polyamide-6/TiO2 composite nanofibers on silicon substrate was in the range of 1∼3 μA, and about 1 to 20 pA for the paper and glass substrates.